Examining the Relationship between Alopecia Areata, Androgenetic Alopecia, and Emotional Intelligence. Issue 1 (January 2013) - Monselise, Assaf; Bar-On, Reuven; Chan, Lisa; Leibushor, Naama; McElwee, Kevin; Shapiro, Jerry
Background: Emotional stress has been associated with the development of alopecia areata (AA) and androgenetic alopecia (AGA). Emotional intelligence (EI), a component of general intelligence, is thought to govern the recognition, expression, and control of stress and other emotions. People with low EI are unable to adequately control stress in everyday life. Objective: To investigate EI differences between AA and AGA patients and a control population. Methods: Thirty-five AGA patients and 42 AA patients, with patchy ( n = 28), ophiasis ( n = 5), totalis ( n = 5), and universalis ( n = 4) distribution of hair loss, completed a 133-item Emotional Quotient-Inventory (EQ-I) psychometric assessment. Scores were compared between AA, AGA, and 77 control subjects obtained from the North American normative population sample on which the psychometric instrument was normed. Results: Statistically significant differences were found in EI between AA patients and controls with the EQ-I Stress Tolerance scale ( p = .005). AGA patients also differed significantly from the controls but to a lesser degree compared toAA patients. In overall EI, there were no apparent differences between AGA and AA patients. Conclusions: AA and AGA patients exhibit a mild depressive reaction to their condition, with AA patients demonstrating a significantly stronger deficiency in coping with stress than AGA patients. The data support a psychosomatic contribution to AA. Referral of patients for EI assessment and psychosocial counseling could help reduce stress.